Analisa Penerapan Metode Atomisasi Air Terhadap Karakteristik Serbuk Alumunium - Taufik Wisnu (Jurnal Optimasi Teknik Industri (JOTI), 2019)
Powder metallurgy is a technology in processing metal powders which includes changing shape, characteristics and the structure became the final metal products. Water Atomization methode is the best option on metal powders production because the most economical and effective. On the large-scale industry, setting the characteristics was important in determining the quality of the powder to the next process. In this reseach performed a series of experiments to produce aluminum powder using water atomization method with variation of the nozzle’s angle 3o, 5o, 10o and 15o. The goal is to find out the influence of the nozzle’s angle and the water pressure sprayer against characteristics of the powder. From the macro structure’s test results showed an average of most grains of pollen produced by the water atomization method is irregular-shaped with porosity that is almost found in pollen in each size. Porosity more found in larger sizes. Observation of microstructure found that the change in composition is relatively small, with declining proportion of Al because Al oxidized by O2 when atomization process while Si proportion was increasing. Nozzle’s angle at 150 give the best powder characteristics with highest percentage of good quality powder and also the highest aspect ratio which means approaching round shape.Keywords: Water Atomization, Powder Metallurgy, Metal Powders, Characteristics of Aluminum powder